Case-control and family-based association studies of candidate genes in autistic disorder and its endophenotypes: TPH2 and GLO1 - Melmed Raun; Schneider Cindy; Trillo Simona; Bravaccio Carmela; Militerni Roberto; Moessner Rainald; Rousseau Francis; Hager Jorg; Papaleo Veruska; Sacco Roberto; Elia Maurizio; Curatolo Paolo; et al. (BMC, 2007)
Abstract Background The TPH2 gene encodes the enzyme responsible for serotonin (5-HT) synthesis in the Central Nervous System (CNS). Stereotypic and repetitive behaviors are influenced by 5-HT, and initial studies report an association of TPH2 alleles with childhood-onset obsessive-compulsive disorder (OCD) and with autism. GLO1 encodes glyoxalase I, the enzyme which detoxifies α-oxoaldehydes such as methylglyoxal in all living cells. The A111E GLO1 protein variant, encoded by SNP C419A, was identifed in autopsied autistic brains and proposed to act as an autism susceptibility factor. Hyperserotoninemia, macrocephaly, and peptiduria represent some of the best-characterized endophenotypes in autism research. Methods Family-based and case-control association studies were performed on clinical samples drawn from 312 simplex and 29 multiplex families including 371 non-syndromic autistic patients and 156 unaffected siblings, as well as on 171 controls. TPH2 SNPs rs4570625 and rs4565946 were genotyped using the TaqMan assay; GLO1 SNP C419A was genotyped by PCR and allele-specific restriction digest. Family-based association analyses were performed by TDT and FBAT, case-control by χ2, endophenotypic analyses for 5-HT blood levels, cranial circumference and urinary peptide excretion rates by ANOVA and FBAT. Results TPH2 alleles and haplotypes are not significantly associated in our sample with autism (rs4570625: TDT P = 0.27, and FBAT P = 0.35; rs4565946: TDT P = 0.45, and FBAT P = 0.55; haplotype P = 0.84), with any endophenotype, or with the presence/absence of prominent repetitive and stereotyped behaviors (motor stereotypies: P = 0.81 and 0.84, verbal stereotypies: P = 0.38 and 0.73 for rs4570625 and rs4565946, respectively). Also GLO1 alleles display no association with autism (191 patients vs 171 controls, P = 0.36; TDT P = 0.79, and FBAT P = 0.37), but unaffected siblings seemingly carry a protective gene variant marked by the A419 allele (TDT P < 0.05; patients vs unaffected siblings TDT and FBAT P < 0.00001). Conclusion TPH2 gene variants are unlikely to contribute to autism or to the presence/absence of prominent repetitive behaviors in our sample, although an influence on the intensity of these behaviors in autism cannot be excluded. GLO1 gene variants do not confer autism vulnerability in this sample, but allele A419 apparently carries a protective effect, spurring interest into functional correlates of the C419A SNP.